The Anabaptists and the Civil Authorities of Strasbourg, 1525-1555 - Kreider, Robert S. 1919-2015 (1955)
Since the dawn of the Christian era the relationship between church and state has been one of the pivotal issues of western civilization. Men have offered a variety of answers to this problem. The much- persecuted Anabaptists of the 16th century presented one set of answers, radical for their age, which called for a decisive separation of the church from the state and complete freedom for the church to pursue its vocation in the world. The Anabaptists were a distressing annoyance to the civil authorities. This movement posed for the 16th century the acute problem: how should religious dissent be handled?
Keywords: Anabaptisten/Wiedertäufer; Neuzeit; Früh; Verhältnis Staat-Kirche; Anabaptists; Modern Era; Early; church-state relations